Patent Failure : How Judges, Bureaucrats, and Lawyers Put Innovators at Risk - Bessen, James, 1958- (Book collections on Project MUSE., 2008)
Presenting a wide range of empirical evidence from history, law, and economics, this text is an authoritative and comprehensive look at the economic performance of patents. It asks whether patents work well as property rights, and, if not, what institutional and legal reforms are necessary to make the patent system more effective.